Edukasi Kesehatan Isi Piringku pada Anak Usia Sekolah di SDN 01 Sangalla Utara Kabupaten Tana Toraja - Hermin Neli; Hayuti Windha Pagiu; Lucia Yogyana Suramas; Fera Dwiyanti (Jurnal Pengabdian Bidang Kesehatan, 2024)
School-aged children need adequate nutrients that support children's growth and development. Children can learn, play and develop optimally which is supported by nutritious and balanced food intake (Marfuah et al., 2022). School-aged or elementary school (SD) children are easily affected by malnutrition. Several factors that cause nutritional problems in school-aged children include parents' economic difficulties and low intake of nutritious food. Apart from that, parents' lack of awareness of the importance of nutrition, irregular eating patterns, and wrong eating habits also have negative effects related to nutrition (Rahmi, 2020). Apart from that, eating disorders such as anorexia or bulimia are related to social pressure, unhealthy body image and other emotional problems. Therefore, there is a need to increase awareness about the importance of healthy eating patterns, provide access to nutritious food, strengthen nutrition education in schools, and involve parents in supporting good eating habits at home, collaboration between parents, schools and communities as well. plays a role in supporting healthy eating patterns for children (Susanti et al., 2024). The aim of this service activity is to increase students' knowledge about the importance of optimal nutritional intake in accordance with children's nutritional needs so that it can support optimal growth and development, producing an intelligent and accomplished generation, therefore it is necessary to carry out health promotion efforts in the form of providing education and evaluation to increasing knowledge about nutrition in school-aged children so as to create a healthy, superior and achieving generation.